A Slang Analysis Used in the Movie “Fast Five” - Pramana, I kadek yuda; I Dewa Ayu Devi Maharani Santika (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
This research explores the slang words used in the film "fast five" through a descriptive-qualitative approach. The aim is to identify and classify the types of slang present in the movie, utilizing the theory proposed by Allan and Burridge (2006). Data collection involved an observational method, which included watching the film, analyzing the dialogue, reading the film's script, and documenting all slang words used by the characters. The study reveals that there are five types of slang in "Die Hart": fresh and creative (32%), flippant (21%), imitating (7%), acronyms (7%), and clipping (21%). The predominant type is fresh and creative slang. The research suggests that the use of slang fosters familiarity within society and the social environment, but it also highlights the importance of understanding these terms to avoid miscommunication in informal conversations